Ethnoscience: Mapping the Potential of Sasak Local Wisdom as a Source of Science Learning - Hunaepi, Hunaepi; Suastra, I Wayan; Arnyana, Ida Bagus Putu; Hasbullah, Hasbullah (Lembaga Penelitian dan Pemberdayaan Masyarakat, 2024)
The integration of Sasak local wisdom into science education, particularly in biology, physics, and chemistry, offers a contextual and meaningful learning experience for students. This study explores the potential of Sasak cultural practices such as Belaq Tangkel, Poteng Rekat, Bau Nyale, and Nyesek to enrich science education. These traditions are linked to scientific concepts, including human reproduction, biodiversity, material physics, and chemical bonding. The research adopts a literature review approach to identify and map the educational potential of Sasak traditions, focusing on their relevance to scientific learning. For instance, Belaq Tangkel introduces students to embryonic development, while Kalender Rowot Sasak supports teaching astronomy. The integration of these practices promotes sustainability values, analytical skills, and cultural appreciation among students. Challenges such as limited resources and teacher training highlight the need for collaboration between educators, local communities, and researchers. This approach not only fosters cultural preservation but also enhances students’ scientific understanding, providing a holistic and sustainable educational framework. The findings underline the importance of ethnoscience in bridging traditional knowledge and modern science to create an inclusive and culturally responsive education system.